Provisions for cost reduction in breeding horse breeding in Ukraine Резервы снижения себестоимости в племенном коневодстве Украины - Kukla Oleg L. (Bìznes Inform, 2012)
The article reserves to reduce the cost justified by the content breeding of horses on farms in Ukraine. Determined the total cost per head of their structure. When milking breed mares manufacturing cost per head of young stock will amount to 22183 UAH , which in 9000 will be lower compared to the option, when the mares are not milked. В статье обоснованы резервы снижения себестоимости при содержании племенных лошадей в хозяйствах Украины. Определены общие затраты на одну голову, их структура. При доении племенных конематок производственная себестоимость одной реализованной головы молодняка составит 22183 грн, что на 9 тыс. ниже по сравнению с вариантом, когда племенные кобылы не доятся.